Retracing Ezzatabad Garden Design - Hamid Reza Jayhani; Leila Akrami (صفه)
Abarkooh is a historic city located in the central Iranian Plateau some 140 kilometers from Yazd City. The multitude of gardens and fields surrounding its fortifications and the historic cypress tree at its center are witness to its long tradition of gardening. The Ezzatabad Garden—also called Omid Salar—is a typical historic suburban garden located close to the main road. Covering an area of 2.7 hectares, it was probably built in the late Qajarid period by Salar Nezam, a local warlord, and named after his son, Omid Salar. It is still privately owned, but is currently abandoned and exposed to decay as its subterranean water sources have dried up. To determine its original design, this paper reviews historic documents, aerial photographs as well as verbal history of the City. In its original design, a wall enclosed the garden with four two-storey towers at each corner. Pathways and patches were symmetrically designed around the main axis leading to the main entrance. There was a two-storey pavilion with an area of approximately 400 sqm on the main axis. Rather than being located at the center, the pavilion was placed closer to the rear wall adding to the air of formality on this axis. The upper storey and the area behind the pavilion were reserved for more private usage, however.